(untitled) (Proceedings of the Society of Antiquaries of Scotland, 2013)
There are ample surviving references in the witchcraft trial material to indicate that the witches’ sabbath became an important feature of the crime of witchcraft in Scotland. Comparison of the trial material has revealed numerous discrepancies between individual and group accounts of the witches sabbath. The frequent inability of the witches to agree upon a time, date or place that the witches’ sabbath took place have indicated that, in the case studied, the witches’ sabbath was not a genuine historical event. Elite beliefs and ideas about the witches’ sabbath were frequently introduced during interrogations, and certainly left their mark upon the witchcraft records. However the examination process was often a negotiation between witches and their interrogators, and as such allowed many witches to incorporate their own beliefs and ideas into their descriptions of the witches’ sabbath. Close reading of the trial material, combined with an analysis of contemporary presbytery records and popular ballads, provides evidence that many witches were drawing upon popular beliefs about fairies, magic and the supernatural, as well as their experiences at real life celebrations and festivities, to compose their descriptions of the witches’ sabbath. The majority of confessions that contain descriptions of the witches’ Sabbath are the product of this interrogation and negotiation process, but this research has also explored the possibility that the witches’ Sabbath might have been a real visionary experience for some witches, and that these visionary experiences were fantasies induced by psychological trauma, or a waking or sleeping vision similar to those experienced by tribal shamans. This research has demonstrated that may pre-existing popular beliefs contributed to the formulation of the witches’ descriptions of the witches’ Sabbath and also stresses the importance of the influence of the interrogation process on the initial presence of the witches’ sabbath in confessions. Although this research has been carried out within the context of Early Modern Scotland, it is likely to have wider implications for the study of the witches’ sabbath in a European context.